Gravity wave momentum flux generation close to mid-latitude Andes in mesoscale simulations of late 20th and 21st centuries - Alexander, Pedro Manfredo (2011)
Adequate representations of diverse dynamical processes in general circulation models (GCM) are necessary to obtain reliable simulations of the present and the future. The parameterization of orographic gravity wave drag (GWD) is one of the critical components of GCM. It is therefore convenient to evaluate whether standard orographic GWD parameterizations are appropriate. One alternative is to study the generation of gravity waves (GW) with horizontal resolutions that are higher than those used in current GCM simulations. Here we assess the seasonal pattern of topographic GW momentum flux (GWMF) generation for the late 20th and 21st centuries in a downscaling using the Rossby Centre regional atmospheric model under the Intergovernmental Panel on Climate Change A1B emission conditions. We focus on one of the world’s strongest extra-tropical GW zones, the Andes Mountains at mid-latitudes in the Southern Hemisphere. The presence of two GCM sub-grid scale structures locally contributing to GWMF (one positive and one negative) is found to the East of the mountains. For the late 21st century the strength of these structures during the GW high season increases around 23% with respect to the late 20th century, but the GWMF average over GCM grid cell scales remains negative and nearly constant around 0.015 Pa. This constitutes a steady significant contribution during GW high season, which is not related to the GWMF released by individual sporadic strong GW events. This characteristic agrees with the fact that no statistically significant variation in GWMF at source level has been observed in recent GCM simulations of atmospheric change induced by increases in greenhouse gases.